A synthetic control chart for monitoring the process mean and variance - Costa, A. F B [UNESP]; Rahim, M. A. (Emerald, 2006)
Purpose - The aim of this paper is to present a synthetic chart based on the non-central chi-square statistic that is operationally simpler and more effective than the joint X̄ and R chart in detecting assignable cause(s). This chart will assist in identifying which (mean or variance) changed due to the occurrence of the assignable causes. Design/methodology/approach - The approach used is based on the non-central chi-square statistic and the steady-state average run length (ARL) of the developed chart is evaluated using a Markov chain model. Findings - The proposed chart always detects process disturbances faster than the joint X̄ and R charts. The developed chart can monitor the process instead of looking at two charts separately. Originality/value - The most important advantage of using the proposed chart is that practitioners can monitor the process by looking at only one chart instead of looking at two charts separately. © Emerald Group Publishing Limted.
Keywords: Control theory; Markov processes; Statistical analysis; System monitoring; Algorithms; Condition monitoring; Process control; Statistical methods; Chi-square statistics; Control charts; Process mean; Variance; Process engineering